Inequity in accessibility to urban parks in environmental gentrification areas based on Multi-G3SFCA: A case study of Wuhan’s main urban districts - Zixuan Deng; Ling Ning (Ecological Indicators)
Equitable access to urban parks is essential for promoting social fairness and sustainable urban development. However, in the context of urban renewal, environmental gentrification has exacerbated inequities in urban park accessibility. Although research on green space equity is relatively rich, studies focusing on inequities in urban park accessibility in environmental gentrification areas and their influencing factors remain limited. This study aims to analyse inequities in urban park accessibility in gentrified areas and explore the effect of physical spatial and socioeconomic factors on these disparities. With Wuhan’s main urban districts as the study area, environmental gentrification areas were identified using bivariate spatial autocorrelation analysis. An improved three-step floating catchment area(Multi-G3SFCA) method was used to assess the inequities in urban park accessibility across residential communities, and the Gini coefficient and Lorenz curve were used to quantify overall inequity in environmental gentrification areas. Finally, the RF-SHAP method was utilised to analyse the factors influencing accessibility inequities among residential communities. The results indicated that: (1) Environmental gentrification in Wuhan’s main urban districts primarily occurs in lakeside and riverside areas. The average Gini coefficients for community and pocket parks were 0.953 and 0.994, respectively, indicating severe inequity. (2) Physical spatial factors (63%) contributed to inequities in urban park accessibility more than socioeconomic factors (37%). Proximity to rail transit and commercial centres contributed 38% and 22% to inequities, respectively, making them the primary determinants. (3) Although socioeconomic factors had a relatively minor overall effect, they directly influenced inequities and interacted with physical spatial factors. Elements such as the proportion of the ageing population and income levels play a notable role. This study enriches the existing research on inequities in urban park accessibility in environmental gentrification areas. It provides valuable insights for the effective management and planning of urban parks in the context of environmental urban renewal and promotes the equitable development of urban green public spaces.